Tobacco Control Policy : Strategies, Successes, and Setbacks. - De Beyer, Joy; Brigden, Linda Waverley, 1946- (World Bank e-Library., 2003)
"Tobacco Control Policy: Strategies, Successes, and Setbacks tells the stories of recent struggles, successes, and setbacks in six countries - Bangladesh, Brazil, Canada, Poland, South Africa, and Thailand - in which fervent and determined effort helped strengthen policies to reduce tobacco use. This collection of experiences in diverse economic, social, and political situations demonstrates the varied and important roles played by activists, health practitioners, policymakers, researchers, NGOs, politicians, and the press."--Jacket.